Adoption of the Mobile Health Screening Programme for Farming Communities: A Study Among Pesticide-Exposed Farmers from North East of Peninsular Malaysia - Zariyantey Abdul Hamid; Zaliha Harun; Syarif Husin Lubis; Nihayah Mohamed; Ismarulyusda Ishak; Hidayatul Fathi Othman; Nur Zakiah Mohd Saat; Mohamad Roff Mohd Noor; Saiful Zaimi Jamil; Jamil Rafaai (penerbit ukm, 2014)
Health awareness promotion among farming communities are important for a sustainable agriculture activities. A crosssectional study was conducted to assess health status among farming communities in Cameron Highlands, Pahang (n = 61) and Bachok and Pasir Puteh, Kelantan (n = 143). Mobile Health Screening Programme composed of assessment of blood glucose, blood cholesterol, haemoglobin, blood pressure, pterygium, lung function and nerve conductive velocity was utilized. Our results indicate that the percentage of Cameron Highland’s farmers with hyperglycaemia, systolic hypertension, diastolic hypertension and anaemia were 8.2%, 14.8%, 11.5% and 8.2%, respectively. However, higher percentage of farmers in Bachok and Pasir Puteh, Kelantan with hyperglycaemia (32.8%), hypercholesterolaemia (83%), anaemia (24.2%) and systolic hypertension (41.9%) were observed. Pterygium was positive for 88.6% of farmers in Cameron Highlands and 94.4% in Bachok and Pasir Puteh. Lung function test shows that 61.7% and 11.4% of farmers in Cameron Highlands had restrictive and obstructive lung, respectively. In Bachok and Pasir Puteh, a total of 19.8%, 55.5% and 23.9% of farmers were found to have obstructive, restrictive and combined obstructive and restrictive lung, respectively. Current Perception Threshold (CPT) value which indicate nerve conductive velocity were signifi cantly increased (p < 0.05) among Cameron Highland’s farmers for both median and peroneal nerve at all frequencies (5 Hz, 250 Hz and 2000 Hz). In Bachok and Pasir Puteh, the values of the CPT for median nerve was signifi cantly increased (p < 0.05) for all frequencies (5, 250 and 2000 Hz). Meanwhile, a signifi cant increased (p < 0.05) was observed for the CPT values for peroneal nerve at the frequencies of 250 and 2000 Hz as compared to control groups. In conclusion, analysis revealed different health problem among the studied farming communities which could be infl uenced by the differences in farming practices. Thus, employed Mobile Health Screening Programme offers a monitoring approach that could highlight the need for suitable health services and awareness programmes for different farming communities.